The Earth's Land Surface : Landforms and Processes in Geomorphology - Gregory, Kenneth J. (London : SAGE Publications, Limited Thousand Oaks, 2010)
Annotation This introductory text details the land surface of the earth in a readable style covering the major issues, key themes and sensitivities of the environments/landscape. Emphasizing the major ideas and their development, each chapter includes case studies and details of influential scientists (not necessarily geomorphologists) who have contributed to the progress of understanding. Providing a very clear explanation of the understanding achieved and of the debates that have arisen, the book is comprised of 12 chapters in four sections: Visualizing the land surface explains and explores the composition of the land surface and outlines how it has been studiedDynamics of the land surface considers the dynamics affecting the earths land surface including its influences, processes and the changes that have occurred Environments of the land surface looks to understand the land surface in major world regions highlighting differences between the areasManagement of the land surface is an examination of the current and future prospects of the management of the earths land surface
Includes Index.
College Audience